THE SHATTARIYA ORDER BETWEEN UNIVERSAL AND LOCAL ISLAM - Sunarwoto Sunarwoto (Millah: Journal of Religious Studies, 2009)
It is commonly viewed that a philologist is one whose job is to provide the readers with ready-to-read texts. In dealing with old manuscripts, he is only concerned with editing and publishing them so that it is the readers’ task to understand, use and even ‘enjoy’ them. However, this is indeed only a small part of a philologist’s work. More significantly, a philologist may contribute to the development of other disciplines such as history, ethnography and other social and humanistic disciplines. This is what Fathurrahman has done in this book.